Pengaruh Metode Permainan Kapal Perang Dan Motivasi Belajar Terhadap Prestasi Belajar Pada Mata Pelajaran IPS Kelas VIII A SMP Negeri 9 Palangka Raya - Susanto, Sumiatie (Meretas: Jurnal Ilmu Pendidikan; Vol 3 No 3 (2016): Jurnal Ilmu Pendidikan Meretas, 2017)
This study raised concerns about effect of the application Battleship Game method and Achievement Motivation Against Student Learning Achiement in social studies in the eighth a grade students of SMP N 9 Palangkaraya Academic Year 2013/2014? Quantitative approaches to the study design, the type of descriptive research with the aim of assessing the effect of the application of IPS Subjects in the eighth grade students of SMP N 9 Palangkaraya Academic Year 2013/2014. This study concludes that there are significant and a significant positive relationship between battleships game method and motivation to study in the field of study in the Junior High School social studies 9 Palangkaraya. Where significant level of 5% is 3.42, the results of the count r ie 6.496 can be concluded that the calculated F is greater than F table so the nil hypothesis is rejected while the alternative hypothesis is accepted or approved which states that there is a significant positive relationship between the warships and game method students' motivation on student achievement social studies class VIII in SMP N 9 Palangkaraya.